Czech Republic : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
After three years of recession, the economy grew by 2.9 percent in 2000, supported by a revival of investment in primarily foreign-owned firms and a modest increase in household consumption. Against the background of a still nascent recovery, fiscal policy was expansionary in 2000, with the general government deficit (excluding privatization receipts and bank restructuring costs) increasing by nearly 1 percentage point to 4.1 percent of GDP. Executive Directors noted that flexibility in the conduct of monetary policy is key to ensuring that inflation remains under control.